A pharmaceutical industry survey results on the cycle time, drivers and enablers, for key deliverables in the early phase of drug product development from dose limiting toxicity to first subject first dose: The survey conducted by the IQ cycle time benchmarking working group - Campbell, Gossett A.; Barrett, Stephanie E.; Thakral, Seema; Lowinger, Michael; Faassen, Fried; Vander Kamp, Kirk A.; Wagner, Daniel; Bargmann-Leyder, Nathalie; Badawy, Sherif; Gaebele, Tracy; Snyder, Phillip (Journal of drug delivery science and technology, 2025)
This paper presents a comprehensive benchmarking analysis of cycle times from Dose Limiting Toxicity (DLT) to First Subject First Dose (FSFD) within the pharmaceutical and biopharmaceutical industry. Conducted by the IQ Consortium Early Phase Cycle Time Benchmarking Working Group (ePCTB WG) under the Drug Product Leadership Group (DPLG), the study aimed to identify key deliverables, enablers, and drivers that influence early drug development timelines across various formulation modalities. Key findings indicate that immediate release tablets/capsules (83 %) and API in capsules (58 %) are the most commonly used oral solid dosage (OSD) forms, with median cycle times of 15 months and 16.5 months, respectively. For small molecule sterile products, intravenous (IV) solutions are predominant with a median cycle time of 17.4 months, while lyophilized formulations show slightly shorter timelines. Large molecule sterile products, including monoclonal antibodies and lipid nanoparticles, also show a preference for IV solutions with a median cycle time of 15 months. The survey highlighted that the longest cycle time across all modalities is the time taken to release the Good Manufacturing Practice (GMP) drug substance, ranging from 6 to 12 months. Companies that initiate GMP drug substance manufacture before the availability of the DLT report tend to have shorter overall cycle times. The study also identified that certain enablers, such as the availability of drug substance and the definition of drug product strengths, significantly impact the initiation of GMP drug product manufacture and GLP toxicology studies. The findings from this manuscript can be utilized by pharmaceutical companies to streamline their early phase drug development processes. By identifying the rate-limiting steps and key enablers, companies can make informed decisions to accelerate timelines, mitigate risks, and enhance efficiency in bringing new drugs to market. The benchmarking data serves as a valuable reference for setting realistic timelines and expectations, ultimately contributing to faster delivery of innovative treatments to patients. [Display omitted] •Detailed benchmarking analysis of cycle times from Dose Limiting Toxicity (DLT) to First Subject First Dose (FSFD).•Results identify key factors influencing early drug development timelines across various formulation types.•The longest cycle time across all modalities is for the release of the GMP drug substance, ranging from 6 to 12 months.•Companies that begin GMP drug substance production before the Dose Limiting Toxicology report have shorter overall cycle times.•Enablers such as drug substance availability and drug product strengths, impacts GMP drug product manufacture and GLP studies.